Preferences for legume attributes in maize-legume cropping systems in Malawi - Waldman, K.B.; Ortega, D.L.; Richardson, R.B.; Clay, D.C.; Snapp, Sieglinde S. (Springer, 2016)
Adoption rates of leguminous crops remain low in sub-Saharan Africa despite their potential role in improving nutrition, soil health, and food security. In this study we explored Malawian farmers’ perceptions of various legume attributes and assessed how these perceptions affected allocation of land to legume crops using a logit link model. We found high regional variation in both consumption- and production-related preferences, but relatively consistent preferences across samples. While scientific understanding and farmer perceptions were aligned on some topics and for some legumes, there were discrepancies elsewhere, particularly in terms of soil fertility and nutrition. Understanding why these discrepancies exist and where there were potential biases are critical in explaining the extent of adoption. In many cases perceptions of legume attributes may be influenced by the cultural role of the crop in the household, particularly in terms of food security or market-orientation. The findings also suggest that researchers need to look beyond both the agronomic properties and farmers’ preferences to fully understand the extent of adoption. Socioeconomic factors, biases, and marketing concerns may also influence integration of legumes into maize-based cropping systems.